Lower urinary tract symptoms and urodynamic findings in children and adults with cerebral palsy: A systematic review - Samijn, Bieke; Van Laecke, Erik; Renson, Catherine; Hoebeke, Piet; Plasschaert, Frank; Vande Walle, Johan; Van den Broeck, Christine (Neurourology and urodynamics, 2017)
Aims To systematically review the scientific literature addressing lower urinary tract symptoms (LUTS) and urodynamic findings in adults and children with Cerebral Palsy (CP). Prognostic factors were also investigated. Methods A systematic research was conducted on the electronic databases PubMed, Web of Science, and CINAHL. Only full text clinical trials which examined the prevalence of LUTS or urodynamic findings in children or adults with CP were eligible. LUTS and urodynamic findings, defined by the International Children's Continence Society, were extracted from the included studies. Pooled average of extracted data was calculated. Studies were scored on methodological and reporting quality using the Dutch Cochrane Checklist, EBRO guidelines, and the Strengthening the Reporting of Observational Studies in Epidemiology Statement (STROBE) checklist. Results Twenty‐seven studies fulfilled selection criteria. Methodological and reporting quality were moderate to low. An average of 55.5% of subjects with CP experience one or more LUTS. Storage symptoms are more common than voiding symptoms due to the high prevalence of neurogenic detrusor overactivity. Patients with voiding symptoms and pelvic floor overactivity are more prone to progress to upper urinary tract dysfunction in adult life. Urodynamic evaluation can direct management. Negative prognostic factors are the spastic subtype with quadriplegic distribution, moderate to severe functional impairment (GMFCS III or higher) and severe cognitive impairment. Conclusion The significant prevalence of LUTS, risk for deterioration, and the impact of urinary tract symptoms on quality of life and health status warrants the need for evaluation and treatment in further research. Neurourol. Urodynam. 36:541–549, 2017. © 2016 Wiley Periodicals, Inc.